Role of Two-Way Asymmetrical Communication in Sustaining Public Relations - Samira Setoutah; Riadh Jeljeli; Faycal Farhi; Mohamed Mallek; Dalia Hassan; Nadeen Selim (Emerging Science Journal, 2024)
Internet technology's worldwide success and adoption have provided organizations with direct access to their constituents and customers. Especially, organizations relying on online platforms provide comparatively better services and have strong relations with their clients. This research also focused on relevant phenomena in the United Arab Emirates banking sector organizations. The researchers employed a cross-sectional design and randomly selected a sample of n=400 individuals. Results revealed a significant impact of customer support services on providing product information (p>0.008) and service quality (p>0.000). Further, the effect of service quality on Artificial Intelligence also remained significant (p>0.000). Besides, Artificial Intelligence is also found significantly impact the Public Relations of Emirati banks (p>0.006). Finally, the mediating impact of communication skills on Artificial Intelligence and Public Relations remained significant (p>0.088). Moreover, the Artificial Neural Network (ANN) revealed the Sum of Square Values at 568.19, the Overall Relative Error value at 0.813, and the accuracy level at 18.7% (training). While, regarding the testing, the Sum of Square Values remained at 256.80 and the Average Overall Relative Error value remained at 0.861, indicating an overall accuracy of 13.9%. Thus, it is concluded that the importance of two-way communication can be determined because it helps determine and understand the customers' needs and demands. The more an organization understands its customers, the more it fulfills their expectations, indicating the importance of two-way communication. Finally, this research recommends more studies regarding AI-enabled Emotional Intelligence in other sectors to dig out in-depth results.